Edukasi pada Remaja tentang Cegah Pernikahan Anak - Asmariana, Yully; Rahayu, Dian; Oktavia, Maria Yasri; Nurwahyuni, Nurwahyuni; Suci, Suci (LPPM Universitas Bumigora, 2024)
Early marriage or marriage at a young age contributes greatly to the high death rate when women first give birth. Data on marriages of children under 16 years of age as many as 9.23% still occur in child marriages. It has indeed decreased from 10.28% in 2019 and 10.35% in 2020. The purpose of this community service is to provide socialization and to educate society, particularly teenagers about preventing early marriage in Singkawang City. The method of implementing service is carried out by providing education which is followed by teenagers in Singkawang City. The results obtained in this activity were the knowledge value before and after education with a value of 47.3 and experienced an increase of 97.3. This youth education contains positive values, by postponing marriage until the 'mature' age, is more important. The impact of this community service is expected to reduce the percentage of early marriage and to support them to get a brighter future.